GSK3β and Tau Protein in Alzheimer’s Disease and Epilepsy - Toral-Rios, Danira; Pichardo-Rojas, Pavel S.; Alonso-Vanegas, Mario; Campos-Peña, Victoria (Frontiers in Cellular Neuroscience, 2020)
Alzheimer's Disease (AD) is the most common form of dementia present in older adults; its etiology involves genetic and environmental factors. In recent years, epidemiological studies have shown a correlation between AD and chronic Epilepsy, since a considerable number of patients with AD may present seizures later on. Although the pathophysiology of seizures in AD is not completely understood, it could represent the result of several molecular mechanisms linked with amyloid beta peptides accumulation (Aβ) and the hyperphosphorylation of tau protein, that may induce an imbalanced in the release and recapture of excitatory and inhibitory neurotransmitters, structural alterations of the neuronal cytoskeleton, synaptic loss and neuroinflammation. These changes could favor the recurrent development of hypersynchronous discharges and epileptogenesis, which in a chronic state favor the neurodegenerative process and influence the cognitive decline observed in AD. Supporting the correlation, histopathological studies in brain tissue of temporal lobe epilepsy (TLE) patients, have revealed the presence of Aβ deposits and the accumulation of tau protein in the neurofibrillary tangles, accompanied by an increase of glycogen synthase kinase 3-beta (GSK3β) activity that may lead to an imminent alteration in post-translational modifications of some microtubule-associated proteins, mainly tau. The present review is focused on understanding the pathological aspects of GSK3β and Tau in the development of TLE and AD.